'Var tackad!' Zu Passivisierungsmöglichkeiten beim schwedischen Verb tacka und dessen Äquivalenten in Polnisch und Deutsch - Zborowski, Piotr (Folia Scandinavica Posnaniensia, 2010)
The paper presents the possibilities of passive transformations in Swedish, German and Polish, which are confronted with each other on the basis of some constructions with the verbs tacka, danken and dziękować. The use of passive is possible with transitive verbs, which – according to the grammatical definition given by Polański (1999) – the Polish dziękować and the German danken are not. For languages where the case system is reduced, like Swedish or English, transitivity may be defined semantically: a verb is transitive if it demands any object. In the case of Swedish it is possible to transform the verb tacka into passive, an example being the passive imperative construction var tackad (eng. be thanked).